Streamlining Upstream Processing of Complex Biopharmaceuticals - Sousa, Marcos (2020)
"The market demand for new biopharmaceuticals is increasing with the aging of the global population and associated (chronic) diseases, rising interest for targeted (cell and gene) therapy, and the advent of new infectious diseases (e.g. Covid-19 pandemics). It becomes evident the need to accelerate the development of commercial processes for the manufacturing of such biopharmaceuticals to meet such demand. This thesis targets such needs creating solid knowledge on the upstream processing of animal cell cultures for the production of complex biopharmaceuticals using bioreactors and microcarriers technology, perfusion and integrated biomanufacturing as optimization tools. The work developed attempted to cover some latitude of challenges based on differences in product characteristics: (i) recombinant protein for drug discovery (human recombinant Bone Marrow Tyrosine kinase on the chromosome X – hrBMX, Chapter 2), (ii) virus as vaccine candidate (Peste des Petites ruminants virus – PPRV – vaccine, Chapter 3), (iii) virus for cancer therapy (oncolytic adenovirus type 5 – OV-Ad5, Chapter 4), and (iv) stem cells for cell therapy (human Mesenchymal Stem Cells – hMSC, Chapter 4). System’s complexity was embraced using bioreactors scale-down models and bioengineering correlations defining optimal process operation and scale-up.(...)"